BUTTERFLY DIVERSITY (LEPIDOPTERA: PAPILIONOIDEA) IN KALOY LIMESTONE HILL, TAMIANG HULU DISTRICT, ACEH TAMIANG REGENCY - Nurjannah, Nurjannah; Putri, Kartika Aprilia; Sari, Herlina Putri Endah; Persada, Andri Yusman; Fajar, Beni Al (Masyarakat Zoologi Indonesia, 2023)
Studies on butterflies have been done in Aceh region, like Aceh Besar, Aceh Selatan, Aceh Tengah, and Langsa. But there is no research about butterfly from Aceh Tamiang, especially in Kaloy. There are many habitat types in Kaloy, one of them is Kaloy Limestone Hills (KLH) with many vegetation in there that support butterfly diversity. This research aims to analyze butterfly diversity from KLH. Field observations were conducted from December 2022 – January 2023 (in the end of rainy season) using the standard walk method with six observation sessions. The result showed there were 32 species belonging to four families, with Nymphalidae as the most families found and Junonia hedonia as the most species found. The ecological assessment of butterfly populations at the time of the research were butterfly diversity indexes (H’) were between 2.24-2.46 and the dominance indexes (D) were between 0.11-0.13. Butterfly diversity from KLH is additional information to butterfly database in Indonesia, especially Aceh Province. Also, this information can be a future reference for conservation management in Kaloy.